Technical Note - Injuries Associated With Continuous Miners, Shuttle Cars, Load–Haul–Dump And Personnel Transport In New South Wales Underground Coalmines (The National Institute for Occupational Safety and Health (NIOSH))
In the three years to June 2005, 959 injuries associated with continuous miners (CMs), shuttle cars (SCs), load-haul-dump and personnel transport (PT) were reported by NSW underground coal mines, comprising 23% of all injuries reported. The present paper reports an analysis of the narrative field accompanying these reports to determine opportunities for controlling injury risks. The most common combinations of activity and mechanism were: strain while handling CM cable (96 injuries); caught between or struck by moving parts while bolting on a CM (86 injuries); strains while bolting on CM (54 injuries); and slipping off a CM during access, egress or other activity (60 injuries). For the other equipment considered, the common injury mechanism was the vehicle running over a pothole or other roadway abnormality causing the driver or passengers to be injured (169 injuries). Potential control measures include: monorails for CM services; hydraulic cable reefers; handrails on CM platforms; redesign of CM platforms and bolting rigs to reduce reach distances during drilling and bolting; improvements to guarding of bolting controls; standardisation and shape coding of bolting controls; two handed fast feed; improvements in underground roadway maintenance, vehicle suspension, visibility and seating; and pedestrian proximity warning devices.